Assignments In Insurance Law - Venugopal, A Vijayalakshmi (Journal of Malaysian and Comparative Law, 2002)
The concept of assignments in insurance law takes on many forms - firstly due to the various branches of insurance law and secondly due to the variuos components in an insurance transaction that can be assigned. The format of this discussion, therefore, is reflective of this framework. Assignment are first discussed in the context of the following branches of insurance law: (i) marine insurance, (ii) property insurance, (iii) motor insurance, and (iv) life insurance. The next stage of this discussion focuses on what may be assigned in an insurance transaction and how such assignments are legally effected, namely, the assignment of: (a) an insurance policy; (b) the proceeds of an insurance policy; and (c) the subject matter of an insurance policy.